Exploring the dynamics of network characteristics for Indian high technology entrepreneurial firms - Bharat Bhushan; Sharadindu Pandey (Journal of Global Entrepreneurship Research, 2015)
Recent research acknowledges that networking constitutes an important aspect of entrepreneurial efforts for any organization. This aspect takes up an even bigger role in case of high technology firms that are in their growth phases. This exploratory study is an attempt to understand as to how various network characteristics evolve and contribute to the growth and success of any entrepreneurial firm in the Indian socio-cultural context. Specific focus was on exploring four important characteristics of firm network: Network Diversity, Network Inertia, Network Endorsement and Network Relational Mix. Entrepreneurs of ten Indian high-technology firms from National Capital region (NCR) were involved by explaining them the context of this study through intensive face to face discussions and asked to share their experiences using a descriptive questionnaire. The questions were framed around four network variables to be studied. Qualitative responses were received from seven of the ten entrepreneurs within the defined time frame. The inputs from these seven respondents were analysed using explanation building approach for case study analysis. Some of the findings of the study go well with the extant literature, thereby contributing to theory validation for Indian socio-cultural context. However, several new aspects came up whereby the findings don't seem to go well with the existing theories thereby leading to potential areas to be explored further. Such variations are discussed in the conclusion section and summarized point by point with respect to existing models. These could be potential areas of further study in the current context.
Keywords: 650; Entrepreneurship; Networks; Network characteristics; Organizationgrowth; Co-evolution; Diversity; Inertia; Endorsement; Relational mix